Dyeing of cotton with madder using (bio)mordants: effects on fastness and UV protection properties - Alves, Cátia; Fernandes, Marta; Rodrigues, Rui; Zille, Andrea (Wydawnictwo Politechniki Łódzkiej, 2022)
This work aimed at studying the dyeing of cotton fabrics with madder extract using two biomordants, quebracho tree extract (Schinopsis spp.) and laccase. Pre-treatment with quebracho increased the colour strength, washing and UV light fastness, and UV protection, while laccase only shows an increase in the UV light fastness. The application of biomordants together with the metal ones (aluminium or iron salts) led to an improved UV light fastness compared to the samples mordanted only with metal salts. Meanwhile, although the colour strength was lower than in the metal-mordanted samples, greater UV protection factors were obtained in the samples pre-treated with quebracho or laccase and iron salt.
Keywords: natural dyeing; Rubia tinctorum L.; metal complex; tannin; laccase; naturalne barwniki; kompleks metali; tanina; lakaza